2016
DOI: 10.1055/s-0036-1571285
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoking and Smoking Cessation on Spine Surgery: A Systematic Review of the Literature

Abstract: Study Design Literature review. Objective The aim of this literature review was to detail the effects of smoking in spine surgery and examine whether perioperative smoking cessation could mitigate these risks. Methods A review of the relevant literature examining the effects of smoking and cessation on surgery was conducted using PubMed, Google Scholar, and Cochrane databases. Results Current smokers are significantly more likely to experience pseudarthrosis and postoperative infection and to report lower clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 72 publications
2
65
0
1
Order By: Relevance
“…These results are consistent with previously published data describing a significant negative association between smoking and spine surgery outcomes. 52 …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previously published data describing a significant negative association between smoking and spine surgery outcomes. 52 …”
Section: Discussionmentioning
confidence: 99%
“… 13 Other studies showed preoperative smoking cessation for 4 weeks is associated with a decreased risk of infection, perioperative respiratory, and wound complications. 14 - 16 Thus, it would be necessary to refrain from smoking at least 4 weeks before surgery and 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age, non-smoking status, high preoperative NDI score, and low postoperative NRS score for the arm were observed to be significantly different in those who were subjectively satisfied. A systematic review showed that the effectiveness of cervical and lumbar surgery in smokers is lower than that in non-smokers [ 18 ]. Our results were consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%